Superficial tuberculous lymphadenitis in Merseyside: 1969-1984. - Wilkins, E. G. (Cambridge University Press, 1985)
The aetiology, epidemiology and clinical presentation of 137 bacteriologically confirmed cases of superficial mycobacterial lymphadenitis identified at the Liverpool Public Health Laboratory between 1969 and 1984 were reviewed. Despite a fall in pulmonary and total extrapulmonary isolates, the annual recovery of mycobacteria from lymph nodes remained relatively constant. Mycobacterium tuberculosis was the cause of infection in 121 patients (88.3%), M. bovis in 6 and the remaining 10 isolates were atypical mycobacteria. In European patients (68.6%) the highest incidence was in the elderly, whereas in non-Europeans (31.4%) the disease almost exclusively occurred in the third and fourth decades. The proportion of isolates from non-Europeans reflected the size of the immigrant population and increased during the period of study.